The Role of History Teachers in Applying Masohi Cultural Value-Based Learning Materials (Gotong Royong) to Build Student Character at SMAN 3 Ambon City - Touwe, Sem; Putro, Rendy Wahyu Satriyo; Pattiasina, Johan; Ernas, Asrar (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2025)
This study examines the role of history teachers in integrating Masohi (Gotong Royong) cultural values into history lessons at SMAN 3 Ambon City to enhance student character development. The research focuses on five key character indicators: cooperation, social care, responsibility, solidarity, and leadership. A total of 85 students from three classes participated in the study. Data were collected through pre-tests and post-tests, questionnaires, and classroom observations. The results showed significant improvements in student character, with cooperation and responsibility increasing by 30%, solidarity by 29%, social care by 22%, and leadership by 16%. Additionally, the standard deviation decreased, indicating improved consistency in understanding and applying these values among students. This research demonstrates that integrating Masohi values into history education effectively strengthens student character and can serve as a broader model for cultural value-based education in schools across Indonesia.